KETIDAKADILAN JENDER YANG DIALAMI PEKERJA PEREMPUAN DI DAERAH PARIWISATA - WIRARTHA, I MADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Gender isn’t a difference of sex or god’s will, but is something that is oriented him and her by means of social and culture process in long term. The power of woman in tourism sector is very interesting to be solved. According to conventional, tourism sector is public sector, that is a man area, but a woman area is domestic sector. Based on tourism development in Bali, there are many jobs opportunity that can be entered by woman community. In fact it will be affected by gender problem. Gender problem in this paper is studied based on research in two villages which different development tourism at Ubud, Gianyar, Bali. The result of the research shows that the woman worker in tourism sector are discriminated which is reflected by lower level wage than man worker although they have same education and or same job position.
Keywords: Tourism, Gender, Problem